Evaluating the performance of the operation at the sawmill production company - Teng, Lik Ching (2013)
In this study, it discusses about evaluating the performance of the operation at the sawmill production company. The scope of this study is focusing on the production process in sawmill company. The time frame covered is one year it is in the year of 2013. This study is conducted by using the ARENA simulation software to simulate the modeled process in the simulation software. It is a quantitative study in which the performance is measured by the productivity for the whole system of sawmill. The reducing of the waiting time in the bottleneck station able to provide an improvement in the sawmill production process.